2022
DOI: 10.1002/cta.3464
|View full text |Cite
|
Sign up to set email alerts
|

A new family of high gain boost DC‐DC converters with reduced switch voltage stress for renewable energy sources

Abstract: In this paper, a new family of non-isolated boost dc-dc converters with high voltage gains is proposed. The proposed boost topologies exhibit very high voltage gains at moderate duty cycles and lower switch voltage/current stresses with reduced component counts. Here, a total of four new non-isolated boost topologies are proposed using four-terminal PWM high-gain switch cells with an inductor-switch network. Among these four topologies, two converters have identical voltage gain with opposite load voltage pola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…It is seen that the proposed converter outperforms almost all of the competitors except [29] and [38]. This comparison reveals that despite the proposed converter implements one or two higher number of components in comparison with the converters of [23,47,49,50,53]; however, the extra components have a more effective role in voltage gain extension.…”
Section: Performance Comparisonmentioning
confidence: 86%
See 1 more Smart Citation
“…It is seen that the proposed converter outperforms almost all of the competitors except [29] and [38]. This comparison reveals that despite the proposed converter implements one or two higher number of components in comparison with the converters of [23,47,49,50,53]; however, the extra components have a more effective role in voltage gain extension.…”
Section: Performance Comparisonmentioning
confidence: 86%
“…Dual switches concept is another way to increase voltage gain and to decrease voltage/current stresses of the switches that have been applied into both of the transformerless [41][42][43][44][45][46][47][48] and CI-based [49][50][51][52][53] step-up DC-DC converters. In the transformer less converters through active SL cells the high voltage gain is provided.…”
Section: Introductionmentioning
confidence: 99%
“…The capacitance of the proposed converter is calculated using the voltage ripple of the capacitor and the current expressions described during modes of operation as expressed in Equation (11).…”
Section: Components Designmentioning
confidence: 99%
“…Modified boost converters using SL, SC, VM, etc., are reported in literature to increase the gain of conventional boost converters 9–11 . A two‐inductor boost converter with VM and SC cells is reported to increase the voltage gain in Andrade et al 9 A family of high‐gain modified boost converter is reported in Shaw et al 11 In all these converters, even though the gain is increased compared to the conventional boost converters, there is still a limitation on the maximum voltage gain. To overcome this limitation, quadratic gain and modified quadratic gain converters are introduced 12–17 .…”
Section: Introductionmentioning
confidence: 99%
“…In recent times, as per the demands of modern applications, certain highly efficient and reduced switch count structures have been developed with low switch voltage stress for non-isolated high gain DC-DC converters [4]. Some authors summarized the review of certain high step-up non-isolated DC-DC converters [5]- [7].…”
Section: Introductionmentioning
confidence: 99%